Halogen Doping to Control the Band Gap of Ascorbic Acid: A Theoretical Study - Nasidi, Ibrahim Isah; Kaygili, Omer; Majid, Abdul; Bulut, Niyazi; Alkhedher, Mohammad; ElDin, Sayed M. (Amer Chemical Soc, 2022)
Ascorbic acid is an important antioxidant agent that acts as an electron donor and is involved in many physiological processes. Structural modification in ascorbic acid is a subject of extensive biochemical research due to its involvement in a variety of relevant phenomena including electron transport, complex redox reactions, neurochemical reactions, enzymatic reactions, and chemotherapeutic potential. In this work, the structure of ascorbic acid is modified via doping with the first three members of the halogen group to investigate the changes in the electronic structure and spectroscopic parameters using first-principles methods. To obtain the lowest-energy structures, different basis sets in density functional theory (DFT) and Hartree-Fock approaches were employed in the geometry optimization process. The potential energy maps of the structures were computed to study the molecular orientations and their optical and electrical properties. The spectroscopic properties were computed via UV-vis and nuclear magnetic resonance (NMR) spectroscopies to study the effects of doping into the compound. To obtain further insights into the chemical structure, the Fourier transform infrared (FT-IR) spectra of the materials were theoretically investigated. It was found that the band gap is sensitive to doping as we moved from fluorine to chlorine and then to bromine.
Keywords: Density-Functional Method; Vitamin-C; Ft-Ir; Spectra; B3Lyp; Chemistry; Raman; Nmr